MENINGKATKAN KEMAMPUAN MENULIS CERPEN SISWA SMP NEGERI 1 DRIYOREJO MENGGUNAKAN MEDIA KOMIK PADA VIDEO POWTOON: MENINGKATKAN KEMAMPUAN MENULIS CERPEN SISWA SMP NEGERI 1 DRIYOREJO MENGGUNAKAN MEDIA KOMIK PADA VIDEO POWTOON - Diana Fatmawati; Retno Danu Rusmawati (Buana Bastra, 2015)
This research is motivated by the low ability of grade 7 A students of SMP Negeri 1 Driyorejo in learning Indonesian, especially in the Basic Competence of "writing short stories". This study uses video powtoon as a solution to improve short story writing skills. Powtoon videos can also be used for various learning fields other than Indonesian. In this study, the data collection techniques used by the author include interview techniques, documentation techniques, observation techniques, questionnaire or test techniques. Data analysis in this study used a qualitative descriptive technique. The population in this study were students of SMP Negeri 1 Driyorejo and the sample consisted of 9 students. The results of the acquisition of the ability to write short stories for the seventh grade students of SMP Negeri 1 Driyorejo in the first cycle were below average, while the scores in the second cycle were above the average. The results of this study indicate that the ability to write short stories for seventh grade students of SMP Negri 1 Driyorejo can improve after applying comics media to video powtoon. Based on the presentation and the results of the discussion, educators can use video powtoon media to improve the ability to write short stories for class VII students of SMP Negeri 1 Driyorejo in particular and others in general.